Porous carbon material, silicon-carbon negative electrode material, preparation methods of porous carbon material and silicon-carbon negative electrode material, and secondary battery

By optimizing the structure and defect degree of porous carbon materials, the problem of structural damage in the activation process of porous carbon materials in the prior art is solved, and the electronic conductivity and rate performance of silicon carbon negative electrode materials are improved.

CN119833635AActive Publication Date: 2025-04-15SHANDONG SHENGQUAN NEW ENERGY TECH CO LTD

Patent Information

Application Number
CN202510029257.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-04-15
Estimated Expiration
2045-01-08

AI Technical Summary

Technical Problem

The structure of existing porous carbon materials is easily damaged during activation, resulting in a decrease in electronic conductivity and affecting the rate performance of silicon carbon negative electrode materials.

Method used

By controlling the R value in the X-ray diffraction pattern of the porous carbon material and the ID1/IG and ID3/IG ratio in the Raman spectrum, the structure and defect degree of the material are optimized, and porous carbon materials with lower defect content and higher electron conductivity are prepared.

Benefits of technology

The electronic conductivity of porous carbon materials and the rate performance of silicon carbon negative electrode materials are improved, and the cycle life of the battery is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005234178220000201
    Figure BDA0005234178220000201
  • Figure BDA0005234178220000211
    Figure BDA0005234178220000211
  • Figure BDA0005234178220000241
    Figure BDA0005234178220000241
Patent Text Reader

Abstract

The invention relates to a porous carbon material, a silicon-carbon negative electrode material, a preparation method and a secondary battery. The R value in an X-ray diffraction pattern of the porous carbon material is 1.4-5, and the R value is the ratio of the diffraction peak intensity of a (002) crystal face to the background intensity; in a Raman spectrogram of the porous carbon material, the ratio ID1 / IG of the intensity of a D1 peak representing a defect-induced graphite structure to the intensity of a G peak representing a graphite lattice is 0.201-2.859, and the ratio ID3 / IG of the intensity of a D3 peak representing amorphous carbon sp3 hybrid carbon atoms to the intensity of the G peak representing the graphite lattice is 0.336-1.403. By controlling the number of oxygen-containing functional groups, a diffusion channel of lithium ions in the porous carbon material is optimized, so that the lithium ions can reach the surfaces of silicon particles more quickly for reaction, and the rate capability of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of battery negative electrode materials, and in particular relates to porous carbon materials, silicon-carbon negative electrode materials, preparation methods and secondary batteries. Background Art

[0002] With the continuous development of lithium-ion battery technology, silicon-carbon anode materials have become a hot topic of current research due to their potential for high energy density and long cycle life. However, the performance of silicon-carbon anode materials depends largely on the quality of their porous carbon substrate.

[0003] As an important component of silicon-carbon negative electrode materials, porous carbon substrates have various preparation methods, mainly including chemical activation, physical activation and template methods. Among them, the chemical activation method usually uses strong bases (such as KOH), strong acids (such as H3PO4) or salts (such as ZnCl2) as activators, which react with carbon precursors at high temperatures to form pore structures through etching. The physical activation rule mainly uses gases (such as CO2 and water vapor) at high temperatures to react with carbon precursors to form pores through the diffusion and etching of gas molecules. The template rule introduces a template with a specific structure into the carbon precursor in advance, and then obtains porous carbon with a regular pore structure through steps such as carbonization and template removal.

[0004] Although the above method can prepare carbon materials with porous structures, the carbon structure is often damaged to a certain extent during the activation process. This damage will not only lead to a decrease in the strength of the carbon material, but also produce a large number of defects, such as vacancies, dangling bonds, etc. These defects will seriously affect the electronic conductivity of the carbon material, thereby reducing the rate performance of the new silicon-carbon negative electrode prepared using this as the substrate. Rate performance is one of the important performance indicators of lithium-ion batteries, which reflects the performance of the battery at different charge and discharge rates. Poor rate performance means that the performance of the battery will drop significantly during rapid charge and discharge, thereby limiting the application of silicon-carbon negative electrode materials in high-performance lithium-ion batteries. Summary of the invention

[0005] In view of the limitations of the above-mentioned prior art, the present invention aims to provide a porous carbon material and a preparation method thereof, so as to prepare a porous carbon material with lower defect content and higher electronic conductivity. At the same time, a silicon-carbon negative electrode material equipped with the porous carbon material of the present application is also provided to improve the rate performance of the new silicon-carbon negative electrode prepared with the porous carbon material as the substrate.

[0006] In one aspect of the present application, a porous carbon material is provided, wherein the R value in the X-ray diffraction spectrum of the porous carbon material is 1.4 to 5, the R value is the ratio of the diffraction peak intensity of the (002) crystal plane to the background intensity, in the X-ray diffraction spectrum, the peaks and valleys on both sides of the (002) crystal plane diffraction peak are used as common tangents to form a background line, and the (002) crystal plane diffraction peak tangent parallel to the background line is drawn to determine the tangent point, the tangent point intensity is the diffraction peak intensity, and the intensity at the diffraction angle 2θ corresponding to the tangent point on the background line is the background intensity; in the Raman spectrum of the porous carbon material, the ratio of the D1 peak intensity characterizing the defect-induced graphite structure to the G peak intensity characterizing the graphite lattice is I D1 / I G is 0.201~2.859, characterizing amorphous carbon sp 3 The ratio of the D3 peak intensity of the hybridized carbon atoms to the G peak intensity characterizing the graphite lattice is D3 / I G It is 0.336~1.403.

[0007] In some embodiments, the R value in the X-ray diffraction spectrum of the porous carbon material is 2.021-2.387.

[0008] In some embodiments, the porous carbon material has a ratio of the D1 peak intensity representing the defect-induced graphite structure to the G peak intensity representing the graphite lattice in the Raman spectrum. D1 / I G It is 0.773~1.638.

[0009] In some embodiments, the porous carbon material is characterized by amorphous carbon sp in Raman spectroscopy. 3 The ratio of the D3 peak intensity of the hybridized carbon atoms to the G peak intensity characterizing the graphite lattice is D3 / I G It is 0.691~0.899.

[0010] In some embodiments, the particle size of the porous carbon material is 0.337-0.365 nm.

[0011] In some embodiments, the length La of the graphene basal plane in the porous carbon material is 2.98 to 4.57 nm.

[0012] In some embodiments, the length La of the graphene basal plane in the porous carbon material is 3.59-4.14 nm.

[0013] In some embodiments, the BET specific surface area of ​​the porous carbon material is 978 to 1324 m 2 / g.

[0014] In some embodiments, the BET specific surface area of ​​the porous carbon material is 1032 to 1213 m2 / g.

[0015] In some embodiments, the average pore diameter of the porous carbon material is 3.41-3.89 nm.

[0016] In some embodiments, the average pore diameter of the porous carbon material is 3.44-3.77 nm.

[0017] In some embodiments, the resistivity of the porous carbon material is 0.007 to 0.079 Ω·cm.

[0018] In another aspect of the present application, a method for preparing the porous carbon material is provided, comprising the following steps:

[0019] The porous template is pretreated by soaking it in a metal salt solution;

[0020] The pretreated porous template is placed in a reactor and heated to a carbon deposition temperature;

[0021] introducing a carbon-containing gas at a carbon deposition temperature for vapor deposition;

[0022] The porous carbon material is obtained by removing the porous template.

[0023] In some embodiments, the porous template is cleaned, dried and / or activated prior to soaking.

[0024] In some embodiments, the porous template is cleaned with ethanol, vacuum dried and / or activated at high temperature before immersion.

[0025] In some embodiments, the porous template is selected from zeolite, copper foam, silica, magnesium oxide, magnesium hydroxide, or calcium oxide.

[0026] In some embodiments, the porous template is selected from zeolites.

[0027] In some embodiments, the metal salt is selected from one or more of ferric chloride, molybdenum chloride, lanthanum chloride, nickel chloride, cobalt chloride, and calcium chloride.

[0028] In some embodiments, the metal salt is selected from lanthanum chloride.

[0029] In some embodiments, the carbon-containing gas is a mixed gas of a carbon precursor gas and argon gas.

[0030] In some embodiments, the carbon precursor gas is selected from CO, CH4, C2H2, C2H6, C3H8, C4H 10 , C2H4, C3H6, C4H8, C6H6, C7H8, C2H6O, etc.

[0031] In some embodiments, the carbon-containing gas has a volume fraction of 5% C2H2 and 95% Ar.

[0032] In some embodiments, the heating rate to the carbon deposition temperature is 1-10° C. / min.

[0033] In some embodiments, the heating rate to the carbon deposition temperature is 5° C. / min.

[0034] In some embodiments, the carbon deposition temperature is 600-1000°C.

[0035] In some embodiments, the carbon deposition temperature is 900°C.

[0036] In some embodiments, the vapor deposition time is 1 to 3 hours.

[0037] In some embodiments, the porous template is removed by chemical etching, high temperature calcination or physical methods.

[0038] In some embodiments, the porous template is removed by sequentially treating with 10% hydrofluoric acid and 10% hydrochloric acid.

[0039] In another aspect of the present application, a silicon-carbon negative electrode material is provided, wherein the silicon-carbon negative electrode material comprises the porous carbon material and a silicon-based material distributed in the pores of the porous carbon material.

[0040] In some embodiments, the silicon-based material is selected from one or more of nano silicon particles, silicon oxide, silicon alloy or porous silicon.

[0041] In some embodiments, the silicon-based material is selected from nano silicon particles.

[0042] In some embodiments, the silicon-based material is selected from nano silicon particles, and the mass content of the nano silicon particles in the silicon-carbon negative electrode material is 10% to 95%.

[0043] In some embodiments, the silicon-based material is selected from nano silicon particles, and the mass content of the nano silicon particles in the silicon-carbon negative electrode material is 85% to 95%.

[0044] In some embodiments, the silicon-based material is selected from nano silicon particles, and the mass content of the nano silicon particles in the silicon-carbon negative electrode material is 90%.

[0045] In some embodiments, the silicon-carbon negative electrode material further includes a coating layer coated on the surface of the porous carbon material.

[0046] In some embodiments, the coating layer includes a carbon-based material, a conductive polymer, or a metal oxide.

[0047] In some embodiments, the coating layer includes a carbon-based material, and the carbon-based material includes one or more of amorphous carbon, graphite carbon, carbon nanotubes, and carbon fibers.

[0048] In some embodiments, the coating layer includes a conductive polymer, and the conductive polymer includes one or more of polyaniline (PANI), polypyrrole (PPy), and polythiophene (PTh).

[0049] In some embodiments, the coating layer includes a metal oxide, and the metal oxide includes one or more of aluminum oxide (Al2O3), titanium dioxide (TiO2), and silicon dioxide (SiO2).

[0050] In another aspect of the present application, a method for preparing the silicon-carbon negative electrode material is provided, comprising the following steps: placing the porous carbon material in a reactor, heating it to a silicon deposition temperature under an inert gas environment, and introducing a gas phase silicon source for silicon deposition.

[0051] In some embodiments, the reactor comprises a rotary kiln or a fluidized bed.

[0052] In some embodiments, the silicon deposition temperature is 450-1000°C.

[0053] In some embodiments, the silicon deposition temperature is 550°C.

[0054] In some embodiments, the temperature is increased to the silicon deposition temperature at a heating rate of 5-10° C. / min.

[0055] In some embodiments, the silicon deposition time is 600 min to 4000 min.

[0056] In some embodiments, the inert gas has an inlet flow rate of 3 L / min to 16 L / min.

[0057] In some embodiments, the gas-phase silicon source is selected from at least one of monosilane (SiH4), disilane (Si2H6), trichlorosilane (SiHCl3), dichlorosilane (SiH2Cl2), and tetrachlorosilane (SiCl4).

[0058] In some embodiments, the gas-phase silicon source is selected from monosilane (SiH4).

[0059] In some embodiments, the inlet flow rate of the gas-phase silicon source is 1 L / min to 2 L / min.

[0060] In some embodiments, the method for preparing the silicon-carbon negative electrode material comprises the following steps:

[0061] The porous carbon material is placed in a reactor, heated to a silicon deposition temperature under an inert gas environment, and a gas phase silicon source is introduced to perform silicon deposition;

[0062] The inert gas flow rate is maintained and a gas-phase carbon source is introduced to perform carbon deposition.

[0063] In some embodiments, the gaseous carbon source is selected from CO, CH4, C2H2, C2H6, C3H8, C4H 10 , C2H4, C3H6, C4H8, C6H6, C7H8, C2H6O, etc.

[0064] In some embodiments, the flow rate of the gas-phase carbon source is 1 to 3 L / min.

[0065] In some embodiments, the temperature of the carbon deposition is 550°C.

[0066] In some embodiments, the carbon deposition time is 60 to 120 minutes.

[0067] In another aspect of the present application, a secondary battery is provided, wherein the secondary battery comprises the silicon-carbon negative electrode material.

[0068] In some embodiments, the secondary battery is selected from a lithium ion battery, a lithium polymer battery, or a lead acid battery.

[0069] In some embodiments, the positive electrode material of the secondary battery is selected from lithium cobalt oxide, lithium nickel manganese cobalt oxide or lithium iron phosphate.

[0070] Beneficial effects of this application:

[0071] The present application provides a novel porous carbon material, which maintains a high specific surface area by controlling the R value in the X-ray diffraction spectrum of the porous carbon material to be 1.4 to 5, and also provides a good pore structure and connectivity, which is conducive to the rapid diffusion and storage of lithium ions. D1 / I G The ratio is in the range of 0.2 to 3. By controlling the degree of defects in the porous carbon material, the active sites of the material can be increased, and its activity in the electrochemical reaction can be improved, while the overall structure of the material will not be damaged due to excessive defects. D3 / I G 0.336~1.403, I D3 / I G The value is positively correlated with the number of oxygen-containing functional groups in the porous carbon material. Low oxygen-containing functional groups help reduce the sites that hinder the diffusion of lithium ions, optimize the diffusion channels of lithium ions in the porous carbon material, and enable lithium ions to reach the surface of silicon particles more quickly for reaction, thereby improving the rate performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0072] Figure 1 It is a schematic diagram for determining the R value of the porous carbon material of the present application. DETAILED DESCRIPTION

[0073] The technical scheme of the present application will be clearly and completely described below in conjunction with specific embodiments, but it will be appreciated by those skilled in the art that the following described embodiments are some embodiments of the present application, rather than all embodiments, and are only used to illustrate the present application, and should not be considered as limiting the scope of the present application. Based on the embodiments in the present application, all other embodiments obtained by those of ordinary skill in the art without making creative work, all belong to the scope of protection of the present application. Those who do not specify specific conditions in the embodiments are carried out according to normal conditions or conditions recommended by the manufacturer. Those who do not specify the manufacturer for reagents or instruments used are conventional products that can be obtained by commercial purchase.

[0074] In one embodiment of the present application, a porous carbon material is provided, wherein the R value in the X-ray diffraction spectrum of the porous carbon material is 1.4 to 5, and the R value is the ratio of the diffraction peak intensity of the (002) crystal plane to the background intensity. In the X-ray diffraction spectrum, the peaks and valleys on both sides of the (002) crystal plane diffraction peak are used as common tangents to form a background line, and the (002) crystal plane diffraction peak tangent parallel to the background line is drawn to determine the tangent point, and the tangent point intensity is the diffraction peak intensity, and the intensity at the diffraction angle 2θ corresponding to the tangent point on the background line is the background intensity; in the Raman spectrum of the porous carbon material, the ratio of the D1 peak intensity characterizing the defect-induced graphite structure to the G peak intensity characterizing the graphite lattice is I D1 / I G is 0.201~2.859, characterizing amorphous carbon sp 3 The ratio of the D3 peak intensity of the hybridized carbon atoms to the G peak intensity characterizing the graphite lattice is D3 / I G It is 0.336~1.403.

[0075] As the substrate of silicon-carbon anode materials, porous carbon has an important influence on the rate performance of silicon-carbon anode materials. The higher the degree of graphitization of porous carbon, the more favorable the rate performance of silicon-carbon anode materials is, which is shown as I in the Raman spectrum. D1 / I G The smaller the value of is, the better, indicating that the porous carbon has fewer defects. Therefore, the I D1 / I G The ratio is usually below 1.1. However, in the prior art, porous carbon materials are generally prepared by chemical activation, physical activation, etc. The activation process will destroy the carbon structure to a certain extent, produce many defects, and show a relatively high I D1 / I G The ratio (the peak intensity ratio of D1 peak and G peak in Raman spectrum, ID / IG≥1.1) and poor electronic conductivity affect the rate performance of the new silicon-carbon negative electrode prepared with this as the substrate.

[0076] The applicant found that the number of single carbon layers and oxygen-containing functional groups in the porous carbon structure also affect the rate performance of the silicon-carbon negative electrode formed by the porous carbon. The applicant characterized the R value in the X-ray diffraction spectrum of the porous carbon material as 1.4-5, which indirectly reflected the number of stacked carbon layers. By controlling I D3 / I G value, limiting the oxygen-containing functional groups and overcoming the I D1 / I G Specifically, by controlling the R value in the X-ray diffraction pattern of the porous carbon material to be 1.4 to 5, the porous carbon forms a unique microstructure, which not only maintains a high specific surface area, but also provides good porosity and connectivity, which is conducive to the rapid diffusion and storage of lithium ions. D3 / I G The ratio is in the range of 0.691 to 0.893, indicating that there are lower oxygen-containing functional groups in porous carbon. Fewer oxygen-containing functional groups reduce defects and active sites in porous carbon materials, which usually hinder the diffusion of lithium ions. Therefore, by reducing the number of oxygen-containing functional groups, the diffusion channels of lithium ions in porous carbon materials can be optimized, allowing lithium ions to reach the surface of silicon particles more quickly for reaction, thereby improving the rate performance of the battery.

[0077] In the present application, the R value in the X-ray diffraction pattern of the porous carbon material is obtained by X-ray diffraction (XRD) with Cu Kα radiation (λ=0.15406 nm) (Rigaku SmartLab SE; Rigaku). Figure 1 As shown, a background line is formed by making a common tangent line on the peaks and valleys on the left and right sides of the (002) peak, and then a tangent line is made on the (002) peak, which is parallel to the background line. The point of intersection between the tangent line and the (002) peak is determined, and the intensity corresponding to the point of intersection is recorded as the diffraction peak intensity (B). The diffraction angle corresponding to the point of intersection is determined, and the intensity of the background line at the diffraction angle is recorded as the background intensity (A). The ratio of B / A is determined as the value of the parameter R.

[0078] In this application, the D1 peak is located at about 1350 cm in the Raman spectrum. -1A characteristic peak near 1500cm, which is mainly attributed to disordered structures or defects in carbon materials. These defects can include vacancies, substitutional impurities, edge effects, etc. The presence and intensity of the D1 peak are usually related to the degree of graphitization of the carbon material, the number and type of lattice defects. The D3 peak is usually located at about 1500cm in the Raman spectrum. -1 A characteristic peak near 1580 cm-1 is linearly related to the oxygen-containing functional groups in amorphous carbon. -1 The G band is due to the stretching vibration of the sp2 carbon atom pair (E2g symmetry), representing a perfect graphitized carbon structure. Specifically, the D1, D3 and G peaks were detected using a Renishaw inVia Raman microscope equipped with a 532 nm wavelength laser.

[0079] In some embodiments, the R value in the X-ray diffraction spectrum of the porous carbon material is 2.021-2.387. Specifically, the stacking number can be 2.021, 2.079, 2.137, 2.195, 2.253, 2.311, 2.329, 2.347, 2.365, 2.387.

[0080] In certain embodiments, the porous carbon material has a ratio of the D1 peak intensity representing the defect-induced graphite structure to the G peak intensity representing the graphite lattice in the Raman spectrum. D1 / I G is 0.773 to 1.638. Specifically, I D1 / I G It can be 0.773, 0.858, 0.943, 1.028, 1.113, 1.198, 1.283, 1.368, 1.453, and 1.638.

[0081] In some embodiments, the particle size of the porous carbon material is 0.337-0.365 nm. Specifically, the particle size can be 0.337 nm, 0.339 nm, 0.341 nm, 0.343 nm, 0.345 nm, 0.347 nm, 0.349 nm, 0.351 nm, 0.352 nm, 0.354 nm, 0.356 nm, 0.358 nm, 0.360 nm, 0.361 nm, 0.362 nm, 0.363 nm, 0.364 nm, 0.365 nm.

[0082] In the present application, particle size, also known as particle size or diameter, refers to the size of a material particle. When a certain physical property or physical behavior of a particle to be measured is closest to a homogeneous sphere of a certain diameter, the diameter of the sphere is taken as the equivalent particle size of the particle to be measured. For spherical particles, their size is usually directly expressed in diameter. For non-spherical particles, the concept of equivalent particle size is used to describe their size. Since the shape of actual particles is usually non-spherical, it is difficult to directly express their size in diameter. Therefore, in the field of particle size testing, equivalent particle size is usually used to describe the size of non-spherical particles. Equivalent particle size refers to when a particle's physical property or physical behavior is closest to a homogeneous sphere of a certain diameter, the diameter of the sphere is taken as the equivalent particle size of the particle to be measured. In the present application, particle size can be measured by Mastersizer3000 laser particle size analyzer of Malvern Instruments Ltd., UK.

[0083] In some embodiments, the length La of the graphene basal plane in the porous carbon material is 2.98-4.57 nm. Preferably, the length La of the graphene basal plane in the porous carbon material is 3.59-4.14 nm. Specifically, the length La can be 2.98 nm, 3.07 nm, 3.16 nm, 3.25 nm, 3.34 nm, 3.43 nm, 3.52 nm, 3.59 nm, 3.61 nm, 3.7 nm, 3.79 nm, 3.88 nm, 3.97 nm, 4.06 nm, 4.14 nm, 4.24 nm, 4.33 nm, 4.42 nm, 4.51 nm, 4.56 nm, 4.57 nm. Controlling the length of the graphene basal plane in the porous carbon material can form a relatively continuous conductive network, which is beneficial to the rapid transmission of electrons in the silicon-carbon negative electrode material, and helps the rapid and uniform diffusion of lithium ions between the graphene basal plane and silicon particles, thereby improving the charge and discharge performance of the silicon-carbon negative electrode material. The graphene basal plane of moderate length can form a stable structure, which helps to alleviate the volume change of silicon particles during the charge and discharge process.

[0084] In the present application, the graphene basal plane refers to a planar structure with a two-dimensional structure composed of graphene as the main component or containing graphene fragments in a porous carbon material. These structures may be composed of a single layer or multiple layers of graphene sheets, and may have different edge structures (such as armrest-type or zigzag). The length of the graphene basal plane refers to the maximum size of the plane area along a specific direction (such as the longest axis direction). The length can be measured by scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray diffraction (XRD) and other techniques. Specifically, the length La of the graphene basal plane is detected by X-ray diffraction (XRD), (Rigaku SmartLab SE; Rigaku), and the (002) peak located at about 2θ~26° is profile-fitted and analyzed, and La is calculated using the Scherrer equation. k is the Scherrer constant (k=1.84 for La), λ is the radiation wavelength, β is the half-height width of the (002) reflection, and θ is the reflection angle of (002).

[0085] In some embodiments, the BET specific surface area of ​​the porous carbon material is 978 to 1324 m 2 / g, preferably, the BET specific surface area of ​​the porous carbon material is 1032-1213m 2 / g. Specifically, the BET specific surface area of ​​the porous carbon material can be 978m 2 / g, 987m 2 / g、996m 2 / g, 1005m 2 / g、1014m 2 / g、1023m 2 / g, 1032m 2 / g、1041m 2 / g, 1050m 2 / g, 1059m 2 / g, 1068m 2 / g、1077m 2 / g, 1086m 2 / g, 1095m 2 / g, 1104m 2 / g、1113m 2 / g, 1122m 2 / g, 1131m 2 / g, 1140m 2 / g, 1213m 2 / g, 1324m 2 / g. The BET specific surface area of ​​the porous carbon material is within this range, which significantly enhances the electrochemical activity of the material, improves the transmission efficiency of electrolyte ions, and thus optimizes the energy storage performance. The high specific surface area also means more active sites, which is conducive to further improving the capacity.

[0086] In this application, BET specific surface area refers to the total surface area per unit mass of solid material measured by gas adsorption method based on Brunauer-Emmett-Teller (BET) multi-molecular layer adsorption theory, and the unit is square meters per gram (m 2 / g). The measurement is based on the BET equation, which describes the relationship between the adsorption amount and pressure when gas molecules form multilayer adsorption on the solid surface. The measurement adopts the static volume method. By precisely controlling the temperature and pressure conditions, the sample under test is physically adsorbed with an inert gas (such as nitrogen), the adsorption amount under different pressures is measured, and the specific surface area is calculated using the BET equation. This application uses Micromeritics ASAP 2020 for measurement.

[0087] In some embodiments, the average pore size of the porous carbon material is 3.41-3.89 nm, preferably, the average pore size of the porous carbon material is 3.44-3.77 nm. Specifically, the average pore size of the porous carbon material is 3.41 nm, 3.44 nm, 3.49 nm, 3.53 nm, 3.57 nm, 3.61 nm, 3.65 nm, 3.69 nm, 3.73 nm, 3.77 nm, 3.81 nm, 3.82 nm, 3.84 nm, 3.86 nm, 3.88 nm, 3.89 nm.

[0088] In this application, pore size refers to the diameter of a channel or opening formed in a material (such as metal, plastic, ceramic, composite material, etc.) that allows fluid (such as gas, liquid) or solid particles to pass through. The shape of the pore size can be circular, elliptical, square, rectangular, polygonal or other irregular shapes, depending on the application scenario and processing technology. It is usually regarded as a circle and its radius is used to represent the size of the hole. The size and shape of the pore size need to be accurately measured and verified by equipment such as a microscope, an electron scanning microscope (SEM), a laser rangefinder, and a gas-liquid flow test. Specifically, the pore size is measured using Micromeritics ASAP 2020. The average pore size of the porous carbon material is within this range, which can not only provide sufficient space to alleviate the volume expansion of silicon particles during charging and discharging, effectively extend the battery cycle life, but also promote the rapid diffusion of lithium ions and improve the rate performance of the battery.

[0089] In some embodiments, the resistivity of the porous carbon material is 0.007-0.079Ω·cm. Specifically, the resistivity is 0.007Ω·cm, 0.015Ω·cm, 0.023Ω·cm, 0.031Ω·cm, 0.039Ω·cm, 0.047Ω·cm, 0.055Ω·cm, 0.063Ω·cm, 0.071Ω·cm, and 0.079Ω·cm. In this application, the porous carbon material is pressed into a block structure using a Yuanneng Technology compaction density meter, and then the resistance of the powder is tested using a full set of ceramic molds and a four-probe mode, and the data is taken under a pressure of 100MPa.

[0090] In another embodiment of the present application, a method for preparing a porous carbon material is provided, comprising the following steps: pre-treating a porous template by immersing it in a metal salt solution; placing the pre-treated porous template in a reactor and heating it to a carbon deposition temperature; introducing a carbon-containing gas at the carbon deposition temperature for vapor deposition; and removing the porous template to obtain the porous carbon material.

[0091] The porous carbon material is prepared by vapor deposition using a template method, wherein the porous template is heated to a carbon deposition temperature. This step is intended to preheat the template so that it reaches a state suitable for the deposition of carbon-containing gases. Control of the heating rate is essential to maintaining the integrity and stability of the template structure, and to avoid adverse effects of too fast or too slow heating rates on the template. Under the carbon deposition temperature conditions, a carbon-containing gas is introduced for deposition, and this process is the core of preparing porous carbon materials. The carbon-containing gas decomposes at high temperatures and is deposited in the pores of the template to form a carbon layer. By adjusting parameters such as the deposition time and the type and concentration of the carbon-containing gas, the thickness of the carbon layer and the degree of retention of the pore structure can be precisely controlled. Finally, the porous template is removed by chemical etching, pyrolysis or other methods to obtain a porous carbon material with a uniform pore structure and good electrical conductivity.

[0092] In certain embodiments, the porous template is cleaned, dried and / or activated before heating. Preferably, it includes ethanol cleaning, vacuum drying and / or high temperature activation. Specifically, the porous template is completely immersed in anhydrous ethanol, gently shaken or ultrasonic cleaning equipment is used to fully infiltrate and disperse the impurities and residues on the surface of the template. The cleaning time depends on the degree of contamination and pore structure of the template, and is generally recommended to be between 5 and 30 minutes. Repeat the cleaning 1 to 2 times to ensure thorough cleaning. The cleaned porous template is placed in a vacuum drying oven, heated to a temperature point lower than the pyrolysis temperature of the template material, and vacuumed to a certain level at the same time, and maintained for a period of time until the template is completely dry. The dried porous template is placed in a high-temperature furnace, heated to an activation temperature (usually higher than the pyrolysis temperature of the template material but lower than its structural destruction temperature), and maintained for a period of time to cause physical and chemical changes on the surface and inside of the template, such as removing residual impurities and increasing porosity.

[0093] In certain embodiments, the porous template is selected from zeolite, foamed copper, silicon dioxide, magnesium oxide, magnesium hydroxide or calcium oxide, but considering the connectivity of the porous carbon skeleton and the adjustability of the pore structure, preferably, the porous template is selected from zeolite. Zeolite is a class of microporous crystalline aluminosilicate materials, and there are more than 200 types of structure types. Each structure type has its own unique pore structure, such as pore size, shape and connectivity. At present, zeolites have microporous zeolites, mesoporous zeolites and macroporous zeolites, so the pore size and wall thickness of the deposited porous carbon can be customized according to the pore size and wall thickness of the zeolite. The pore diameters in many zeolites are suitable for accommodating fullerenes and carbon nanotubes, and they are interconnected along smooth curved surfaces to form a three-dimensional (3D) network open to the outside. In principle, this nanoporous system should be an ideal template for synthesizing 3D graphene structures. Another important characteristic of zeolites is their ion exchange capacity. The zeolite framework contains cations to compensate for the negative charge of aluminum in the tetrahedral silicate framework. The synthesized cations are usually sodium or ammonium ions, which can be exchanged with other cations through traditional solution-based ion exchange processes, which is beneficial for the adsorption of catalyst ions during subsequent impregnation with other catalyst solutions.

[0094] In some embodiments, the metal salt is selected from one or more of ferric chloride, molybdenum chloride, lanthanum chloride, nickel chloride, calcium chloride, and cobalt chloride. Preferably, the metal salt is selected from lanthanum chloride. Metal salt ions can be adsorbed in the pores of the porous template, reducing the temperature required for the decomposition of the carbon source, facilitating the deposition of the carbon source inside the template pore structure, reducing the deposition on the template surface, and forming a high-quality porous carbon material.

[0095] In some embodiments, the carbon-containing gas is a mixture of a carbon precursor gas and argon gas, and the carbon precursor gas is selected from CO, CH4, C2H2, C2H6, C3H8, C4H 10 , C2H4, C3H6, C4H8, C6H6, C7H8, C2H6O, etc. Preferably, the carbon-containing gas is selected from C2H2, and specifically, the volume fraction content of the carbon-containing gas is: 5% C2H2, 95% Ar.

[0096] In some embodiments, the heating rate to the carbon deposition temperature is 1 to 10°C / min. Preferably, the heating rate to the carbon deposition temperature is 5°C / min. Specifically, the heating rate to the carbon deposition temperature is 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min.

[0097] In some embodiments, the carbon deposition temperature is 600-1000°C. Preferably, the carbon deposition temperature is 900°C. Specifically, the carbon deposition temperature is 600°C, 630°C, 660°C, 690°C, 720°C, 730°C, 740°C, 750°C, 760°C, 770°C, 780°C, 790°C, 800°C, 805°C, 810°C, 815°C, 820°C, 825°C, 830°C, 835°C, 840°C, 845°C, 850°C, 855°C, 860°C, 865°C, 870°C, 875°C, 880°C, 885°C, 890°C, 900°C, 910°C, 920°C, 930°C, 940°C, 950°C, 960°C, 970°C, 980°C, 990°C, 1000°C, 1010°C, 1015°C, 1020°C, 1025°C, 1030°C, 1035°C, 1040°C, 1050°C, 1060°C, 1070°C, 1080°C, 1090°C, 1110°C, 1111°C, 1120°C 5℃, 870℃, 875℃, 880℃, 885℃, 890℃, 895℃, 900℃, 905℃, 910℃, 915℃, 920℃, 925℃, 930℃, 935℃, 940℃, 945℃, 950℃, 955℃, 960℃, 965℃, 970℃, 975℃, 980℃, 985℃, 990℃, 995℃, 1000℃. The increase of deposition temperature increases the graphitization degree of the deposited graphite layer and reduces defects, which is beneficial to improve the first coulomb efficiency, reduce the resistivity of the porous carbon powder, and increase the conductivity of the obtained porous carbon deposited silane, which is beneficial to improve the rate performance of the silicon-carbon negative electrode. However, if the temperature is too high, the carbon source will not enter the interior of the template and will be deposited on the surface, which will be detrimental to the formation of open pores and the deposition of silane.

[0098] In some embodiments, the vapor deposition time is 1 to 3 hours. Specifically, the vapor deposition time is 1 hour, 1.5 hours, 2 hours, 2.5 hours, and 3 hours. Increasing the deposition time and the number of deposited carbon layers will help to improve the strength of the carbon skeleton, further offset the stress generated by the volume expansion of the lithium battery during the charging and discharging process, and avoid the collapse of the carbon skeleton, thereby increasing the service life of the material. However, if the deposition time is too long, the number of deposited carbon layers will increase and the carbon source will be deposited on the template surface.

[0099] In some embodiments, the porous template is removed by chemical etching, high temperature calcination or physical method. Preferably, 10% hydrofluoric acid and 10% hydrochloric acid are used in sequence to remove the porous template. Before the porous template is formally removed, the sample is cleaned with a solvent such as deionized water or ethanol to remove impurities and contaminants on the surface. Hydrofluoric acid can effectively dissolve silicate materials such as silicon dioxide. The sample is immersed in a hydrofluoric acid solution, and the reaction time and temperature are controlled to ensure the complete dissolution of the template. In some cases, hydrochloric acid can be used to further remove residues or adjust the surface properties of the porous carbon material. After etching is completed, the sample is neutralized with deionized water or an alkaline solution (such as sodium hydroxide solution) to remove residual acid. Then the sample is cleaned with deionized water again. For some templates that cannot be effectively removed by chemical etching, a high temperature calcination method can be used. The sample is placed in a high temperature furnace, heated to a high temperature at an appropriate heating rate, and kept warm for a period of time to ensure complete combustion or decomposition of the template. After removing the template, the porous carbon material may also need to be post-processed to further optimize its performance. For example, an activating agent (such as water vapor, carbon dioxide, etc.) is used to activate the porous carbon material to increase its specific surface area and porosity.

[0100] In another embodiment of the present application, a silicon-carbon negative electrode material is provided, wherein the silicon-carbon negative electrode material includes the porous carbon material and a silicon-based material distributed in the pores of the porous carbon material.

[0101] In some embodiments, the silicon-based material is selected from one or more of nano silicon particles, silicon oxides, silicon alloys or porous silicon. Preferably, the silicon-based material is selected from nano silicon particles. The theoretical specific capacity of silicon is much higher than that of graphite (about 10 times that of graphite), so the use of nano silicon particles can significantly improve the energy density of lithium ion batteries. Nano-scale silicon particles have a larger specific surface area, which can effectively shorten the diffusion path of lithium ions from the electrolyte to the inside of the active material and improve the charge and discharge rate. Although silicon undergoes significant volume expansion (about 300%) during the lithiation process, nano-sizing can alleviate this problem to a certain extent, because small-sized particles are more easily adapted to volume changes and reduce the risk of cracking and pulverization. Compared with pure silicon, the Li2O formed by silicon oxides (such as SiO, SiO2, etc.) during the lithiation process can serve as a buffer matrix, effectively absorb part of the volume expansion stress, and improve the cyclic stability of the material. The irreversible Li2O layer formed when silicon oxides are charged for the first time can reduce lithium loss in the first cycle, thereby improving the first coulomb efficiency. By alloying with other metals (such as magnesium, tin, copper, etc.), silicon alloys with lower volume expansion coefficient and higher conductivity can be formed, thereby significantly improving cycle stability and rate performance while maintaining high capacity; alloying can also adjust the lithiation / delithiation potential of the material, which helps to avoid side reactions with components in the electrolyte and prolong battery life. The porous structure provides additional space for the volume expansion of silicon, reduces structural damage caused by volume change, and thus improves cycle stability. The combination of one or more of nano-silicon particles, silicon oxide, silicon alloy or porous silicon can give full play to their respective advantages to achieve high energy density, good cycle stability and excellent rate performance. For example, the combination of nano-silicon particles and silicon oxide can improve cycle stability through the formed Li2O layer while maintaining high capacity; the introduction of silicon alloys can further adjust the working potential, reduce side reactions, and reduce volume expansion effects; the addition of porous silicon further optimizes volume expansion management and lithium ion transmission efficiency. This composite strategy provides broad space and possibilities for the development of high-performance silicon-carbon negative electrode materials.

[0102] In certain embodiments, the silicon-based material is selected from nano silicon particles, and the mass content of the nano silicon particles in the silicon-carbon negative electrode material is 10% to 95%. Preferably, the mass content of the nano silicon particles in the silicon-carbon negative electrode material is 85% to 95%. More preferably, the mass content of the nano silicon particles in the silicon-carbon negative electrode material is 90%. Specifically, the mass content of the nano silicon particles in the silicon-carbon negative electrode material is 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%.

[0103] In another embodiment of the present application, a silicon-carbon negative electrode material is provided, wherein the silicon-carbon negative electrode material includes the porous carbon material and a silicon-based material distributed in the pores of the porous carbon material, and a coating layer coated on the surface of the porous carbon material.

[0104] In some embodiments, the silicon-based material is selected from one or more of nano silicon particles, silicon oxide, silicon alloy or porous silicon. Preferably, the silicon-based material is selected from nano silicon particles.

[0105] In certain embodiments, the silicon-based material is selected from nano silicon particles, and the mass content of the nano silicon particles in the silicon-carbon negative electrode material is 10% to 95%. Preferably, the mass content of the nano silicon particles in the silicon-carbon negative electrode material is 85% to 95%. More preferably, the mass content of the nano silicon particles in the silicon-carbon negative electrode material is 90%. Specifically, the mass content of the nano silicon particles in the silicon-carbon negative electrode material is 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%.

[0106] In some embodiments, the coating layer includes a carbon-based material, preferably, the carbon-based material includes one or more of amorphous carbon, graphite carbon, carbon nanotubes, and carbon fibers. Although amorphous carbon has a low degree of crystallinity, its good electrical conductivity can significantly improve the overall electronic transmission performance of the silicon-carbon negative electrode material, which is beneficial to the high-rate charge and discharge of the battery. The coating of amorphous carbon can effectively fill the micropores and defects on the surface of the porous carbon material, enhance the structural integrity of the material, and reduce the structural damage caused by volume expansion during the charge and discharge cycle. Graphite carbon itself has good lithium storage performance, and as a coating layer, it can increase the overall capacity of the negative electrode material. Carbon nanotubes have excellent electrical conductivity and one-dimensional structure, and can form a conductive network on the surface of the silicon-carbon negative electrode material, accelerate the transmission of lithium ions, and improve the charge and discharge performance of the battery; at the same time, the high mechanical strength of carbon nanotubes helps to improve the overall mechanical properties of the negative electrode material and resist the stress caused by volume changes during the charge and discharge process. Carbon fiber has good toughness and strength. As a coating layer, it can significantly improve the crack resistance and anti-pulverization ability of the negative electrode material and extend the service life of the battery.

[0107] In some embodiments, the coating layer includes a conductive polymer, and the conductive polymer includes one or more of polyaniline (PANI), polypyrrole (PPy) and polythiophene (PTh). The introduction of conductive polymers significantly improves the conductivity of silicon-carbon negative electrode materials. Polyaniline (PANI), polypyrrole (PPy) and polythiophene (PTh) all have good conductivity. They can form a uniform conductive network on the surface of porous carbon materials, effectively reducing the transmission resistance of electrons inside the material, thereby improving the charge and discharge rate and efficiency of the battery. And it can be tightly coated on the surface of porous carbon materials to form a protective barrier, effectively preventing the electrolyte from corroding porous carbon materials and silicon-based materials, while reducing the stress caused by volume expansion and contraction during the charge and discharge process, thereby improving the cycle stability and service life of the material.

[0108] In some embodiments, the coating layer includes a metal oxide, and the metal oxide includes one or more of aluminum oxide (Al2O3), titanium dioxide (TiO2) and silicon dioxide (SiO2). Aluminum oxide, titanium dioxide and silicon dioxide are all inorganic materials with high hardness, which can form a solid protective layer on the surface of porous carbon materials, effectively preventing cracks and pulverization caused by volume expansion and contraction of silicon-based materials during charging and discharging, thereby extending the cycle life of negative electrode materials. These metal oxides also have good chemical stability and thermal stability, can resist the erosion of organic solvents and lithium salts in the electrolyte, prevent the negative electrode material from having side reactions with the electrolyte, and reduce the risk of thermal runaway, thereby improving the safety performance of the battery. It is worth noting that although silicon dioxide (SiO2) itself does not have high lithium ion conductivity, it can react with lithium under certain conditions to generate compounds such as lithium silicate (Li4SiO4), which can further alleviate the volume expansion of silicon-based materials and provide a certain capacity contribution. Therefore, under certain conditions, the introduction of silicon dioxide can also have a positive effect on the performance of silicon-carbon negative electrode materials.

[0109] In another embodiment of the present application, a method for preparing the silicon-carbon negative electrode material is provided, comprising the following steps: placing the porous carbon material in a reactor, heating it to the silicon deposition temperature under an inert gas environment, and introducing a gas-phase silicon source for gas silicon deposition. The use of an inert gas is intended to prevent the porous carbon material and the subsequent gas-phase silicon source from undergoing oxidation or hydrolysis reactions at high temperatures, thereby maintaining the purity and structural integrity of the material. The silicon deposition temperature is generally higher than the gasification temperature of the silicon source but lower than the pyrolysis temperature of the porous carbon material to ensure that the silicon source can be fully vaporized and uniformly deposited in the pores of the porous carbon material, while avoiding damage to the structure of the porous carbon material. When the reactor reaches the set temperature, a gas-phase silicon source (such as silane, silicon tetrachloride, etc.) is introduced for gas silicon deposition, and the gas-phase silicon source undergoes decomposition or reduction reaction at high temperature, and the generated silicon atoms or silicon-based compounds are deposited in the pores of the porous carbon material to form a silicon-based material. This method uses vapor deposition to evenly distribute silicon-based materials in the pores of porous carbon materials, which can effectively alleviate the stress generated by volume expansion and contraction of silicon-based materials during charging and discharging, thereby improving the structural stability and cycle life of silicon-carbon negative electrode materials.

[0110] In certain embodiments, the reactor includes a rotary kiln or a fluidized bed. The rotary kiln rotates so that the porous carbon material in the rotary kiln can be continuously and evenly exposed to the gas phase silicon source, ensuring the uniform deposition of the silicon-based material in the pores of the porous carbon material. This dynamic process helps to reduce local overheating and uneven deposition during the deposition process, thereby improving the uniformity and deposition efficiency of the material. In the fluidized bed, the porous carbon material is fluidized by the gas to form a fluid-like state, which enables the gas phase silicon source to more effectively contact the porous carbon material and undergo a deposition reaction. The high mass transfer efficiency of the fluidized bed helps to achieve rapid and uniform deposition of silicon-based materials.

[0111] In some embodiments, the temperature is increased to 550° C. at a heating rate of 5 to 10° C. / min. Specifically, the heating rate is 5° C. / min, 6° C. / min, 7° C. / min, 8° C. / min, 9° C. / min, or 10° C. / min.

[0112] In some embodiments, the silicon deposition time is 600 to 4000 min. Specifically, the silicon deposition time is 600 min, 800 min, 1000 min, 1200 min, 1400 min, 1600 min, 1800 min, 2000 min, 2200 min, 2400 min, 2600 min, 2800 min, 3000 min, 3200 min, 3400 min, 3600 min, 3800 min, 3900 min, 3950 min, 4000 min. Prolonging the deposition time is beneficial to increase the loading amount of active materials, thereby improving the specific capacitance of the electrode. However, too long a deposition time may also cause the silicon layer to be too thick, causing severe volume expansion of silicon during lithium insertion, causing pulverization of active material particles, destroying the SEI film formed on the surface, resulting in increased internal resistance of the electrode and increased capacity decay. Within the above deposition time range, it is ensured that the silicon layer can fully load the active materials and improve the specific capacitance, while not causing volume expansion and pulverization of the active materials due to excessive thickness, effectively avoiding the increase of the internal resistance of the electrode and the aggravation of capacity decay, and significantly improving the cycle stability and service life of the electrode.

[0113] In some embodiments, the inert gas has an inlet flow rate of 3 to 16 L / min. Specifically, the inert gas has an inlet flow rate of 3 L / min, 5 L / min, 7 L / min, 9 L / min, 11 L / min, 13 L / min, 15 L / min, or 16 L / min.

[0114] In some embodiments, the gas phase silicon source is selected from at least one of monosilane (SiH4), disilane (Si2H6), trichlorosilane (SiHCl3), dichlorosilane (SiH2Cl2), and tetrachlorosilane (SiCl4). Preferably, the gas phase silicon source is selected from monosilane (SiH4). Monosilane is a highly active gas that can rapidly decompose and deposit silicon at relatively low temperatures. Due to its high reactivity and low molecular weight, monosilane can more easily penetrate into the pores of porous carbon materials to achieve uniform deposition of silicon-based materials, which helps to improve the specific capacity and cycle stability of silicon-carbon negative electrode materials.

[0115] In some embodiments, the flow rate of the gas-phase silicon source is 1 L / min to 2 L / min.

[0116] In another embodiment of the present application, a method for preparing the silicon-carbon negative electrode material is provided, comprising the following steps: placing the porous carbon material in a reactor, heating it to the silicon deposition temperature under an inert gas environment, introducing a gaseous silicon source for gas silicon deposition; maintaining the inert gas flow rate, and introducing a gaseous carbon source for carbon deposition. After gas silicon deposition, maintaining the inert gas flow rate and introducing a gaseous carbon source for carbon deposition can form an additional carbon protective layer on the surface and in the pores of the silicon-based material. This carbon protective layer can further alleviate the volume expansion and contraction of the silicon-based material during the charging and discharging process, enhance the structural stability of the material, and thus improve the cycle life. At the same time, the deposition of the gaseous carbon source may fill part of the pores of the porous carbon material, but more importantly, by precisely controlling the conditions of carbon deposition (such as temperature, time, type and concentration of the gaseous carbon source, etc.), the pore structure can be finely controlled, which helps to form a more open and uniform pore structure and improve the specific surface area and lithium ion transmission performance of the material.

[0117] In certain embodiments, the gaseous carbon source is selected from CO, CH4, C2H2, C2H6, C3H8, C4H 10 , C2H4, C3H6, C4H8, C6H6, C7H8, C2H6O, etc. One or more. Small molecule carbon sources such as CO and CH4 usually have a high deposition rate and can form a thicker carbon layer in a shorter time. This is particularly beneficial for situations where the surface of silicon-based materials needs to be quickly covered or pores need to be filled. Macromolecular carbon sources such as C2H2, C2H4, and C6H6 may have a lower deposition rate, but can form a more compact and stable carbon structure, which has a positive effect on improving the structural stability and cycle life of the material. The carbon layer structure (such as amorphous carbon, graphitized carbon, etc.) and properties (such as conductivity, hardness, etc.) formed by the deposition of different carbon sources are different. By selecting a suitable carbon source, the overall structure and performance of silicon-carbon negative electrode materials can be regulated to meet different application requirements. For example, amorphous carbon layers usually have good flexibility and buffering properties, which can alleviate the volume expansion of silicon-based materials; while graphitized carbon layers have higher conductivity and lower internal resistance, which helps to improve the charge and discharge rate and energy efficiency of the battery. By combining different types of carbon sources, a silicon-carbon anode material with a multilayer structure can be constructed. This multilayer structure can combine the advantages of different carbon layers and further improve the overall performance and stability of the material. For example, a small molecule carbon source can be used to quickly cover the surface of the silicon-based material, and then a macromolecular carbon source can be used to form a more dense and stable carbon layer. Alternatively, different carbon sources can be used at different deposition stages to form a multilayer structure with specific structures and functions.

[0118] In some embodiments, the flow rate of the gas phase carbon source is 1 to 3 L / min. Specifically, the flow rate of the gas phase carbon source is 1 L / min, 2 L / min, or 3 L / min.

[0119] In some embodiments, the carbon deposition time is 60 to 120 min. Specifically, the carbon deposition time is 60 min, 63 min, 66 min, 69 min, 72 min, 75 min, 78 min, 81 min, 84 min, 87 min, 90 min, 93 min, 96 min, 99 min, 102 min, 105 min, 108 min, 111 min, 114 min, 117 min, 120 min.

[0120] In another embodiment of the present application, a secondary battery is provided, wherein the secondary battery includes the silicon-carbon negative electrode material.

[0121] In some embodiments, the secondary battery can be any one selected from a lithium-ion battery, a lithium polymer battery or a lead-acid battery. These types of batteries have their own advantages and are suitable for different application scenarios. However, from the perspective of energy density, cycle life and environmental protection, lithium-ion batteries are more preferably selected as the carrier of the present technical solution. Lithium-ion batteries have become the mainstream battery technology in the fields of electric vehicles, portable electronic devices, etc. due to their high energy density, long cycle life and low self-discharge rate.

[0122] In some embodiments, the positive electrode material of the secondary battery can be selected from any one of lithium cobalt oxide, lithium nickel manganese cobalt oxide or lithium iron phosphate. Lithium cobalt oxide has high energy density and good cycle performance, but the cost is relatively high; lithium nickel manganese cobalt oxide has higher energy density and lower cost, but the cycle stability may be slightly inferior; lithium iron phosphate is known for its excellent cycle stability and safety, but the energy density is relatively low. According to the specific application requirements and cost considerations, the most suitable positive electrode material can be selected to match the silicon-carbon negative electrode material to achieve the best battery performance.

[0123] In order to make the purpose, technical solutions and advantages of the present application more clearly understood, the present application is further described in detail below in conjunction with specific embodiments.

[0124] Porous carbon materials

[0125] Example 1

[0126] A porous carbon material is prepared by the following method: placing a zeolite template in deionized water, ultrasonically cleaning for 30 minutes to remove impurities and dust on the surface, then soaking the zeolite template in a 1M lanthanum chloride solution to allow lanthanum ions to be ion-exchanged with zeolite to obtain a zeolite template loaded with lanthanum ions, and blowing the zeolite template dry with nitrogen to ensure that the surface is dry and free of moisture. The pretreated zeolite template is placed in a tubular reactor of a high-temperature furnace, and the tube is cleaned with 50 ml / min of purified nitrogen for 30 minutes to ensure that the air in the system is completely replaced, and the furnace is heated to 800°C at a heating rate of 5°C / min, and at 800°C, a carbon-containing gas is introduced into the tube at a flow rate of 30 mL / min, and maintained for 2 hours to deposit carbon in the pores of the zeolite template, and the system is naturally cooled to room temperature under a nitrogen atmosphere, and a sample is collected to obtain a carbon composite material containing a zeolite template. The carbon composite material was placed in a 10% hydrofluoric acid solution and soaked for 24 hours, with regular stirring during the period to remove the silicon component in the zeolite template, and the sample was washed with deionized water until the washing solution was neutral, and the sample was placed in a 10% hydrochloric acid solution and soaked for 12 hours to remove residual metal ions and other impurities, and the sample was washed with deionized water again until the washing solution was neutral. The washed sample was placed in a vacuum drying oven and dried at 80°C for 12 hours, or dried by nitrogen to ensure that the sample was completely dry, and the dried porous carbon material sample was collected.

[0127] Among them, the zeolite template is selected from Y-type zeolite, which is a tetrahedral network structure composed of sodium stone units, forming a supercage, that is, a large cavity with a diameter of 1.3nm. Each supercage is connected to the other four supercages through an opening with a diameter of 0.74nm.

[0128] The carbon-containing gas is a mixture of 5% by volume carbon-containing gas and 95% by volume argon.

[0129] Example 2

[0130] A porous carbon material, the preparation method is the same as that of Example 1, except that: a zeolite template loaded with lanthanum ions is placed in a tubular reactor of a high-temperature furnace, the tube is purged with 50 ml / min of purified nitrogen for 30 minutes to ensure that the air in the system is completely replaced, the furnace is heated to 900°C at a heating rate of 5°C / min, and at 900°C, a carbon-containing gas is introduced into the tube at a flow rate of 30 mL / min and maintained for 2 hours to deposit carbon in the pores of the zeolite template, and the system is naturally cooled to room temperature under a nitrogen atmosphere, and a sample is collected to obtain a carbon composite material containing the zeolite template.

[0131] Example 3

[0132] The preparation method is the same as that in Example 1, except that: the zeolite template loaded with lanthanum ions is placed in a tubular reactor of a high-temperature furnace, the tube is purged with 50 ml / min of purified nitrogen for 30 minutes to ensure that the air in the system is completely replaced, the furnace is heated to 1000°C at a heating rate of 5°C / min, and at 1000°C, a carbon-containing gas is introduced into the tube at a flow rate of 30 mL / min and maintained for 2 hours to allow carbon to be deposited in the pores of the zeolite template. Under a nitrogen atmosphere, the system is naturally cooled to room temperature, and samples are collected to obtain a carbon composite material containing a zeolite template.

[0133] Example 4

[0134] The preparation method is the same as that in Example 2, except that: the zeolite template loaded with lanthanum ions is placed in a tubular reactor of a high-temperature furnace, the tube is purged with 50 ml / min of purified nitrogen for 30 minutes to ensure that the air in the system is completely replaced, the furnace is heated to 900°C at a heating rate of 5°C / min, and at 900°C, a carbon-containing gas is introduced into the tube at a flow rate of 30 mL / min and maintained for 1 hour to allow carbon to be deposited in the pores of the zeolite template. Under a nitrogen atmosphere, the system is naturally cooled to room temperature, and the sample is collected to obtain a carbon composite material containing a zeolite template.

[0135] Example 5

[0136] The preparation method is the same as that in Example 2, except that: the zeolite template loaded with lanthanum ions is placed in a tubular reactor of a high-temperature furnace, the tube is purged with 50 ml / min of purified nitrogen for 30 minutes to ensure that the air in the system is completely replaced, the furnace is heated to 900°C at a heating rate of 5°C / min, and at 900°C, a carbon-containing gas is introduced into the tube at a flow rate of 30 mL / min and maintained for 3 hours to allow carbon to be deposited in the pores of the zeolite template. Under a nitrogen atmosphere, the system is naturally cooled to room temperature, and samples are collected to obtain a carbon composite material containing a zeolite template.

[0137] Example 6

[0138] The preparation method is the same as that of Example 3, except that: the zeolite template is impregnated with a 3M lanthanum chloride solution, and after heating to 1000 degrees, carbon gas is deposited for 5 hours to deposit carbon in the pores of the zeolite template. The system is naturally cooled to room temperature under a nitrogen atmosphere, and the sample is collected to obtain a carbon composite material containing a zeolite template. Then, the porous carbon is obtained by acid washing, and the obtained porous carbon material is graphitized at a temperature of 1500 degrees to obtain a porous carbon material with enhanced skeleton strength.

[0139] Example 7

[0140] The preparation method is the same as that of Example 1, except that the deposition temperature is 600 degrees and the deposition time is 1 hour.

[0141] Example 8

[0142] The preparation method is the same as that of Example 1, except that the zeolite template is impregnated with a metal salt solution with a concentration of 3M, wherein the metal salts are calcium chloride and lanthanum chloride, and the molar ratio of calcium chloride to lanthanum chloride is 1:1.

[0143] Example 9

[0144] The preparation method is the same as that of Example 1, except that the 1M lanthanum chloride solution is changed to a 2M lanthanum chloride solution.

[0145] Comparative Example 1

[0146] A porous carbon material is prepared by the following method: glucose and KOH are added to a KOH aqueous solution in a mass ratio of 1:1. After stirring at 80°C for 6 hours, the mixture is filtered, the solid matter is separated, and it is thoroughly washed with deionized water until the pH value reaches neutral. The sample after ion exchange is dried in a vacuum oven at 80°C for 8 hours. The obtained solid powder is heated to 900°C at 5°C / min in argon and maintained for 1.5 hours. Finally, the obtained sample is immersed in an excess of dilute HCl solution under stirring, then washed with deionized water until the pH is neutral, and dried in a vacuum oven at 80°C for 8 hours to obtain porous carbon.

[0147] Comparative Example 2

[0148] The preparation method is the same as that in Example 1, except that no catalyst is contained, the deposition temperature is 500 degrees, and the deposition time is 5 hours.

[0149] Properties of porous carbon materials

[0150] 1) Number of carbon layers in a single layer arrangement

[0151] The results were obtained by X-ray diffraction (XRD) with Cu Ka radiation (λ=0.15406 nm) (Rigaku SmartLab SE; Rigaku).

[0152] The empirical parameter R is Figure 1 As shown in , it is measured by the ratio of the height of the (002) Bragg peak to the background. Figure 1 As shown in the figure, the common tangent line of the downward convex curves (peak valleys) on the left and right sides of the (002) peak constitutes the background line 1, and then the straight line is translated upward until it is tangent to the (002) peak to determine the tangent point 2, and the intersection of a vertical line drawn downward from the tangent point and the background line 1 is determined as point 3, the height between the tangent point 2 and the X-axis is defined as B, the height between the intersection point 3 and the X-axis is defined as A, and the ratio of B / A is determined as the value of the parameter R.

[0153] 2) Graphene basal plane length

[0154] The (002) peak at about 2θ to 26° was subjected to profile fitting analysis, and La was calculated using the Scherrer equation:

[0155]

[0156] Wherein, k is the Scherrer constant (k=1.84 for La), λ is the radiation wavelength, β is the half-height width of (002) reflection, and θ is the reflection angle of (002).

[0157] 3) Specific surface area, pore volume, and pore diameter.

[0158] The specific surface area, pore volume and pore size of the samples were characterized by analyzing the nitrogen adsorption and desorption isotherms at 77 K (ASAP 2020, Micromeritics, USA).

[0159] 4)I D1 / I G and I D3 / I G

[0160] Raman spectra were recorded with a Renishaw inVia instrument equipped with a 532 nm wavelength laser.

[0161] The Raman spectrum was divided into D1, D2, D3, D4 and G peaks, with the G peak located at 1580 cm -1 The G band is due to the stretching vibration of sp2 carbon atom pairs (E2g symmetry), representing a perfect graphitized carbon structure. -1 The D1 peak at represents defect-induced graphite, I D1 / I G It can represent the graphitization degree of carbon structure, 1500cm -1 The D3 band at is the short-range sp3 carbon vibration response of amorphous carbon. Some adsorbed molecules, molecular fragments and oxygen-containing functional groups lead to the appearance of the D3 band. D3 / I G The ratio is linearly correlated with the content of oxygen-containing functional groups.

[0162] 5) Powder resistivity

[0163] The porous carbon material was pressed into a block structure using a compaction density meter from Yuanneng Technology. The resistance of the powder was then tested using a full set of ceramic molds and a four-probe mode, with data taken at a pressure of 100 MPa.

[0164] 6) Particle size

[0165] The particle size was measured using a laser particle size analyzer, Mastersizer 3000 produced by Malvern Instruments Ltd., UK.

[0166] The test results are shown in Table 1.

[0167] Table 1 Properties of porous carbon materials

[0168]

[0169] As shown in Table 1, in Examples 1 to 3, as the deposition temperature gradually increases, the I D1 / I G Value and I D3 / I G The values ​​all show a decreasing trend. This phenomenon indicates that the increase in deposition temperature promotes the graphitization degree of the porous carbon material structure and leads to a decrease in the number of oxygen-containing functional groups in the material. In the comparison between Example 2 and Examples 4 to 5, it can be found that with the extension of deposition time, the I of the porous carbon material increases. D1 / I G Value and I D3 / I G The values ​​also show a downward trend. This shows that within a certain time range, increasing the deposition time helps to improve the graphitization degree of the porous carbon material and correspondingly reduce the oxygen-containing functional groups in the material. In the comparison between Example 1 and Examples 8 to 9, by changing the concentration of the metal salt solution, the I of the porous carbon material D1 / I G Value and I D3 / I G Specifically, Example 8 uses a mixed solution of calcium chloride and lanthanum chloride to catalyze the porous template, and the concentration is the same as that in Example 1, but the I of the porous carbon material is D1 / I G Value and I D3 / I G In Example 9, by increasing the concentration of the metal salt, the graphitization degree of the prepared porous carbon material is improved, and the number of oxygen-containing functional groups is reduced.

[0170] Silicon Carbon Anode Material

[0171] Example 10

[0172] A silicon-carbon negative electrode material is prepared by the following method: use ethanol or acetone to clean the inside of the reactor, then pass nitrogen at a flow rate of 6L / min to blow dry, and then use a vacuum pump to evacuate to a certain vacuum degree to remove residual moisture and air. 1kg of the porous carbon material of Example 1 is evenly added to the fluidized bed to ensure that the bed is loose and there is no obvious accumulation. Open the nitrogen valve, adjust the flow rate to 3L / min, and continue to pass nitrogen to replace the air in the reactor. Start the heating device and slowly heat to 550°C at a heating rate of 5°C / min. During this process, nitrogen protection is continuously passed. When the temperature reaches 550°C, monosilane gas is started at a flow rate of 2L / min to carry out a thermal decomposition reaction. Keep the temperature and monosilane flow rate unchanged, and react at a constant temperature for 4000min. During this period, check and adjust the gas flow rate regularly to ensure that the reaction is stable. After the constant temperature reaction is completed, the monosilane gas valve is closed, the nitrogen flow rate is kept unchanged, and the gas switching device is adjusted to introduce acetylene gas at a flow rate of 1L / min to carry out the carbon deposition reaction. The constant temperature reaction is continued for 120 minutes, during which the gas flow rate and reaction temperature are also monitored. After the acetylene deposition is completed, the acetylene gas valve is closed, the nitrogen flow rate is kept unchanged, the reactor is slowly cooled, the heating is stopped, and the reactor is allowed to cool naturally to room temperature to prepare a silicon-carbon negative electrode material with a carbon mass ratio of 10wt%.

[0173] Embodiment 11

[0174] A silicon-carbon negative electrode material is prepared by the following method: use ethanol or acetone to clean the inside of the reactor, then pass nitrogen at a flow rate of 6L / min to blow dry, and then use a vacuum pump to evacuate to a certain vacuum degree to remove residual moisture and air. 1kg of the porous carbon material of Example 1 is evenly added to the fluidized bed to ensure that the bed is loose and there is no obvious accumulation. Open the nitrogen valve, adjust the flow rate to 16L / min, and continue to pass nitrogen to replace the air in the reactor. Start the heating device and slowly heat to 550°C at a heating rate of 10°C / min. During this process, nitrogen protection is continuously passed. When the temperature reaches 550°C, monosilane gas is started at a flow rate of 1L / min to carry out a thermal decomposition reaction. Keep the temperature and monosilane flow rate unchanged, and react at a constant temperature for 600min. During this period, check and adjust the gas flow rate regularly to ensure that the reaction is stable. After the constant temperature reaction is completed, the monosilane gas valve is closed, the nitrogen flow rate is kept unchanged, and the gas switching device is adjusted to introduce acetylene gas at a flow rate of 3L / min to carry out the carbon deposition reaction. The constant temperature reaction is continued for 60 minutes, during which the gas flow rate and reaction temperature are also monitored. After the acetylene deposition is completed, the acetylene gas valve is closed, the nitrogen flow rate is kept unchanged, the reactor is slowly cooled, the heating is stopped, and the reactor is allowed to cool naturally to room temperature to prepare a silicon-carbon negative electrode material with a carbon mass ratio of 95wt%.

[0175] Example 12

[0176] The preparation method is the same as that of Example 10, except that the porous carbon material of Example 2 is used as the substrate.

[0177] Embodiment 13

[0178] The preparation method is the same as that of Example 10, except that the porous carbon material of Example 3 is used as the substrate.

[0179] Embodiment 14

[0180] The preparation method is the same as that of Example 10, except that the porous carbon material of Example 4 is used as the substrate.

[0181] Embodiment 15

[0182] The preparation method is the same as that of Example 10, except that the porous carbon material of Example 5 is used as the substrate.

[0183] Example 16

[0184] The preparation method is the same as that of Example 10, except that the porous carbon material of Example 6 is used as the substrate.

[0185] Embodiment 17

[0186] The preparation method is the same as that of Example 10, except that the porous carbon material of Example 7 is used as the substrate.

[0187] Embodiment 18

[0188] The preparation method is the same as that of Example 10, except that the porous carbon material of Example 8 is used as the substrate.

[0189] Embodiment 19

[0190] The preparation method is the same as that of Example 10, except that the porous carbon material of Example 9 is used as the substrate.

[0191] Comparative Example 3

[0192] The preparation method is the same as that of Example 10, except that the porous carbon material of Comparative Example 1 is used as the substrate.

[0193] Comparative Example 4

[0194] The preparation method is the same as that of Example 10, except that the porous carbon material of Comparative Example 2 is used as the substrate.

[0195] Application Examples

[0196] Batteries were assembled using the products prepared in Examples 7 to 12 and Comparative Examples 3 to 4 as negative electrode materials.

[0197] The obtained silicon-based negative electrode material is used as the negative electrode active material, carbon black as a conductive additive, sodium carboxymethyl cellulose and styrene-butadiene rubber in a mass ratio of 1:1 as a binder, and weighed according to the mass content of 90%:4%:6%. At room temperature, put it into a beater for slurry preparation. The prepared slurry is evenly coated on the copper foil. After drying at 60°C in a blast drying oven for 2 hours, it is cut into 8×8mm pole pieces, and then vacuum-dried in a vacuum drying oven at 100°C for 10 hours. The dried pole pieces are then transferred to the glove box for standby use for battery assembly.

[0198] The assembly of the simulated battery was carried out in a glove box containing a high-purity Ar atmosphere, using metallic lithium as the counter electrode and a solution of 1 mole of LiPF6 in ethylene carbonate (EC) / dimethyl carbonate (DMC) (v:v=1:1) as the electrolyte to assemble the battery.

[0199] When assembling the battery, five batteries are prepared for each test, and a total of five sets of data are tested. The final performance is the average value of the five sets of data.

[0200] The performance test of the lithium-ion battery prepared above is carried out:

[0201] The constant current charge and discharge test was carried out at the charge and discharge rate of 0.1C and 0.5C respectively using the CT2001A Blue Dot Battery Test System of Wuhan Blue Electric Electronics Co., Ltd., with a voltage range of 0.03-1.50V (vs. Li+ / Li). Finally, the 0.1C first discharge capacity mAh / g and the first efficiency % were measured, and the 0.5C charge and discharge cycle test was carried out for 100 weeks after 2 weeks of charge and discharge activation at 0.1C and 0.2C, and the capacity retention rate % after 100 cycles at 0.5C high rate was calculated by using the ratio of the 0.5C discharge capacity at the 100th week to the 0.5C discharge capacity at the first week.

[0202] The experimental parameters and effect data of each embodiment and comparative example are listed in the following Table 2.

[0203] Table 2 Properties of silicon-carbon negative electrode

[0204]

[0205] As can be seen from Table 2, the silicon-carbon negative electrode material in the embodiment of the present application shows superior performance in terms of resistance characteristics, initial charge and discharge efficiency, and capacity retention rate under 0.5C / 0.5C conditions compared to Comparative Examples 3 and 4. This advantage is mainly attributed to the fact that the porous carbon material matrix used in the present application has a high degree of graphitization and contains relatively few oxygen-containing functional groups. Specifically, the porous carbon substrates in Comparative Examples 3 and 4 have a high degree of graphitization and a relatively low degree of graphitization. D1 / I G Ratio and I D3 / IG The ratios are all higher than those in the embodiments of the present application, which directly leads to the silicon-carbon negative electrode materials prepared by them having higher resistance values, lower initial charge and discharge efficiency, and lower capacity retention rate.

[0206] It is particularly noteworthy that although the comparative example 4 and the embodiment 17 D1 / I G The ratio is similar, but due to its I D3 / I G The ratio is higher than that of the examples of the present application. This difference significantly affects the initial charge and discharge efficiency and capacity retention rate of the silicon-carbon negative electrode, making the comparative example 4 perform poorly in these two performance indicators. Therefore, it can be inferred that the optimized graphitization degree and the lower content of oxygen-containing functional groups of the porous carbon material matrix in the present application play a key role in improving the comprehensive electrochemical performance of the silicon-carbon negative electrode material.

[0207] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

Claims

1. A porous carbon material, wherein: The R value in the X-ray diffraction spectrum of the porous carbon material is 1.4-5, and the R value is the ratio of the diffraction peak intensity of the (002) crystal plane to the background intensity. In the X-ray diffraction spectrum, the peaks and valleys on both sides of the (002) crystal plane diffraction peak are used as common tangents to form a background line. The (002) crystal plane diffraction peak tangent line parallel to the background line is drawn to determine the tangent point. The tangent point intensity is the diffraction peak intensity, and the intensity at the diffraction angle 2θ corresponding to the tangent point on the background line is the background intensity. In the Raman spectrum of the porous carbon material, the ratio of the D1 peak intensity characterizing the defect-induced graphite structure to the G peak intensity characterizing the graphite lattice is I D1 / I G is 0.201~2.859, characterizing amorphous carbon sp 3 The ratio of the D3 peak intensity of the hybridized carbon atoms to the G peak intensity characterizing the graphite lattice is D3 / I G It is 0.336~1.

403.

2. A porous carbon material according to claim 1, wherein the porous carbon material comprises at least one of the following features a1) to a3): a1) the R value in the X-ray diffraction spectrum of the porous carbon material is 2.021 to 2.387; a2) the ratio of the D1 peak intensity representing the defect-induced graphite structure to the G peak intensity representing the graphite lattice in the Raman spectrum of the porous carbon material. D1 / I G 0.773~1.638; a3) The porous carbon material characterizes amorphous carbon sp in Raman spectrum 3 The ratio of the D3 peak intensity of the hybridized carbon atoms to the G peak intensity characterizing the graphite lattice is D3 / I G It is 0.691~0.

899.

3. A porous carbon material according to claim 1, wherein the porous carbon material comprises at least one of the following features b1) to b5): b1) the particle size of the porous carbon material is 0.337 to 0.365 nm; b2) the length La of the graphene basal plane in the porous carbon material is 2.98 to 4.57 nm; b3) The BET specific surface area of ​​the porous carbon material is 978 to 1324 m 2 / g; b4) the average pore size of the porous carbon material is 3.41 to 3.89 nm; b5) The resistivity of the porous carbon material is 0.007 to 0.079 Ω·cm.

4. The method for preparing the porous carbon material according to any one of claims 1 to 3, comprising: The porous template is pretreated by soaking it in a metal salt solution; The pretreated porous template is placed in a reactor and heated to a carbon deposition temperature; introducing a carbon-containing gas at a carbon deposition temperature for vapor deposition; The porous carbon material is obtained by removing the porous template.

5. The preparation method according to claim 4, comprising at least one of the following features c1) to c5): c1) the metal salt is selected from one or more of ferric chloride, molybdenum chloride, lanthanum chloride, nickel chloride, cobalt chloride and calcium chloride; c2) the porous template is selected from zeolite, foamed copper, silicon dioxide, magnesium oxide, magnesium hydroxide or calcium oxide; c3) the carbon-containing gas is a mixed gas of a carbon precursor gas and argon gas; c4) the carbon deposition temperature is 600-1000°C; c5) The time of the vapor deposition is 1 to 3 hours.

6. The preparation method according to claim 5, wherein the carbon precursor gas is selected from CO, CH4, C2H2, C2H6, C3H8, C4H 10 , C2H4, C3H6, C4H8, C6H6, C7H8, C2H6O or more.

7. A silicon-carbon negative electrode material, comprising the porous carbon material according to any one of claims 1 to 3 or the porous carbon material obtained by the preparation method according to any one of claims 4 to 6, and a silicon-based material distributed in the pores of the porous carbon material.

8. The silicon-carbon negative electrode material according to claim 7, comprising at least one of the following features d1) to d3): d1) the silicon-based material is selected from one or more of nano silicon particles, silicon oxide, silicon alloy or porous silicon, and preferably the silicon-based material is selected from nano silicon particles; d2) the silicon-based material is selected from nano silicon particles, and the mass content of the nano silicon particles in the silicon-carbon negative electrode material is 10% to 95%; d3) The silicon-carbon negative electrode material further includes a coating layer coated on the surface of the porous carbon material.

9. The silicon-carbon negative electrode material according to claim 8, wherein the coating layer comprises a carbon-based material, and the carbon-based material comprises one or more of amorphous carbon, graphite carbon, carbon nanotubes, and carbon fibers; The coating layer includes a conductive polymer, and the conductive polymer includes one or more of polyaniline, polypyrrole and polythiophene; The coating layer includes metal oxide, and the metal oxide includes one or more of aluminum oxide, titanium dioxide and silicon dioxide.

10. A secondary battery comprising the silicon-carbon negative electrode material according to any one of claims 7 to 9.

Citation Information

Patent Citations

  • Carbon material, cell electrode material, and cell

    CN105408248A

  • Supported catalyst and method for producing a porous graphitized carbon material covered with metal nanoparticles

    CN106457214A

  • Ball-flower-shaped graphene material as well as preparation method and application thereof

    CN115440977A

  • Silicon-carbon composites with enhanced electrochemical properties

    CN116323480A

  • Negative pole piece, electrochemical device and electronic equipment

    CN116848656A

Cited By

  • Silicon-carbon negative electrode composite preparation process for in-situ growth of nano silicon particles

    CN120607238A